Sustainability of Eco-Friendly OCBIP Research to Improve Performance in Organizational Environment: A Literature Review - Desti Ranihusna; Suharnomo (Universitas Darussalam Gontor, 2024)
The purpose of writing this article was to review or summarize and discuss the role of Organizational Citizenship Behavior of Islam Perspective (OCBIP), as an effort factor in improving performance in organizations and and a living environment based on the Quran. The environment as a place to live, particularly for creatures that exist such as humans, including workers. OCBIP is Organizational Citizenship Behavior (OCB) that refers to the Islamic perspective. This type of research is a literature review, using Publish or Perish software. The initial data was an article published from 2010 - 2022. Furthermore, the selection of articles according to the criteria was carried out, and resulted in 28 articles that we would analyze in this study by mapping several criteria and processing the analysis using Vosviewer. The results of the study explained that OCBIP is the behavior of contributing or performing more to others than oneself since basically the best of the people are those who are beneficial to humans. OCBIP was mostly studied as a dependent variable even though some studies showed OCBIP can mediate or independent other variables. The location of the research was mostly conducted in countries that have a majority Muslim population such as Asia and Arabia. This study would provide advantages for the future research on OCBIP. This study provides an overview of research trends regarding OCBIP, especially on Job Performance.